Análisis bibliométrico de la literatura publicada sobre efectos adversos farmacológicos en Web of Science (1981 - 2019) - Diaz Barrera, Mario Enrique (2023)
To perform a bibliometric analysis of the scientific literature published in Web of Science 1981 - 2019 related to pharmacological adverse effects Methods: A search strategy was developed from Pubmed thesauri, Embase and related articles focusing on pharmacological adverse effects. The search was performed in the Core Collection of Web of Science and was restricted to the following documentary types: "Article", "Review", "Proceeding paper", "Letter" and "Meeting Abstract", as well as the period between 1981 and 2019. The results obtained were imported into InCites for the analysis of its production, impact and collaboration indicators. Results: Scientific production has grown at a slower pace in the last 10 years. Academic institutions lead in scientific production, and impact according to accumulated citations and values of "Category Normalized Citation Impact". The institutions with the highest percentage of collaboration (international or corporate) achieve the highest scientific production and number of citations. Discussion: The presented study offers a broader analysis of the topic than those found in previous studies. Conclusions: The recent increased trend towards collaboration has encouraged the participation of various types of institutions in the development of more research with better levels of impact.